Enhancing anti-corruption character through VBL on response text: A case study - Arumtyas Puspitaning Padmasari; Aqiel Ajiz Alfaris; Renda Aranggraeni; Dedi Setiawan; Victor Mt. L. Tobing; Nuril Huda; Daniel Arseneault (Universitas Muhammadiyah Malang, 2025)
Corruption poses a significant challenge in Indonesia, adversely affecting various sectors, including the economy, politics, education, and society at large. Corruption has become ingrained as a culture, character, and mindset within Indonesian society, a phenomenon inherited since the colonial era. This study investigates the effectiveness of video-based learning through short films in enhancing response text about anti-corruption character education for 7th-grade junior high school students in Sidoarjo. It also aims to analyze the impact of the video-based learning method on students' understanding of anti-corruption values and to identify the supporting and inhibiting factors for its implementation. The qualitative research employs a case study approach, focusing on 30 students writing in Response text after watching the short film